Mi van a megtérésen túl? I. rész: A lelki formálódás teológiai alapjai - Lilla SZABÓNÉ LÁSZLÓ (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2023)
What is beyond conversion? Part I. The theological foundations of spiritual formation